Numerical simulation of the three‐dimensional dynamics of healthy and hardened red blood cells passing through a stenosed microvessel by immersed boundary‐lattice Boltzmann method - Hann‐jeng Hsieh (Engineering Reports, 2021)
Abstract Red blood cells (RBCs) infected by a malaria‐like disease can change their membrane stiffness and deformability drastically. The objective of this article is to study the three‐dimensional dynamics of healthy and hardened red blood cells passing through a stenosed microchannel in a Poiseuille flow by combining the immersed boundary and lattice Boltzmann methods. We numerically simulate the transient motion of cells of different degrees of membrane stiffness and observe that hardened cells require a longer traverse time to squeeze through the constriction. We found that, compared with a healthy cell, a hardened cell shows much less change in its bending behavior. We also analyzed the projected deformation index and the velocity profiles of the cells passing through the constricted vessel. Different values of viscosity contrast are examined and show a minor effect on the passage time and bending energy change. In addition, a previous study of the dynamics of a group of three RBCs passing through a constricted microchannel is extended to three‐dimensional in the current work.